Intraepithelial lymphocytes are associated with epithelial injury in feline intestinal T-cell lymphoma - UCHIDA, Kazuyuki; GOTO-KOSHINO, Yuko; CHAMBERS, James K; II, Tatsuhito; NAKASHIMA, Ko (Journal of Veterinary Medical Science, 2024)
Our previous study indicated that cytotoxicity of intraepithelial lymphocytes is a poor prognostic factor in feline intestinal T-cell lymphoma (FITL), but the effect of cytotoxic lymphocytes on mucosal epithelium is still unknown. Thus, we investigated the association between cytotoxic lymphocytes and mucosal epithelium in 71 cases of feline intestinal T-cell lymphoma (FITL): epithelial injury, basement membrane injury, cleaved-caspase-3 positivity of epithelial cells, and the number and Ki67 positivity of intraepithelial lymphocytes in granzyme B (GRB)+ and GRB- FITLs were evaluated. Epithelial injury score and the number of intraepithelial lymphocytes in granzyme B (GRB)+ FITL were significantly higher than those of GRB- FITL (P<0.05, P<0.05), but no significant differences were found in the basement membrane injury score, the percentage of cleaved-caspase-3+ epithelial cells, and the percentage of Ki67+ intraepithelial lymphocytes. There was a significant correlation between the epithelial injury score and the number of intraepithelial lymphocytes (P<0.05), but no significant correlation was observed between the epithelial injury score and Ki67+ percentage of intraepithelial lymphocytes. Because epithelial cell cleaved-caspase-3 positivity was observed in FITL, regardless of GRB expression in lymphocytes, GRB-mediated apoptosis may not contribute to epithelial injury in FITL. The association between increased number of intraepithelial lymphocytes and epithelial injury suggests that intraepithelial lymphocytes infiltration may contribute to epithelial injury in FITL.